Application of RP-HPLC method for the simultaneous determination of cetirizine in the presence of quinolones - Hina Shamshad; Agha Zeeshan Mirza (SpringerOpen, 2021)
Abstract Background Present work describes a fast, simple, and sensitive procedure for the simultaneous determination of cetirizine in the presence of quinolones using diclofenac sodium as an internal standard. The present work was designed to analyze these compounds in pharmaceutical and clinical labs being economical for use. Results The mobile phase consisted of the simple composition of methanol, acetonitrile, and water in a ratio of 50:20:30 with a pH adjusted to 3.1 at a flow rate of 1 mL min−1. The UV detection was performed at 225 nm. The linearity was assessed over the range of 2.5-50 μg mL−1 for all drugs. The parameters such as accuracy, precision, linearity (>0.999), and sensitivity were satisfactory. Conclusion The method was equally applicable for formulation and human serum with recovery values between 95 and 105%. The results of the method were validated statistically according to ICH guidelines.